PENGARUH DISIPLIN BELAJAR DAN PEMANFAATAN PERPUSTAKAAN TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS VII DI SMP NEGERI 13 SIJUNJUNG - Susrita, Nila; , S.Pd, ME, Jolianis; Dahen, Lovelly Dwinda (Pendidikan Ekonomi, 2014)
ABSTRACTThis study aimed to determine ( 1 ) the influence of the discipline of learning on learning outcomes of students of SMP Negeri 13 economic Sijunjung ( 2 ) the effect of the use of libraries on learning outcomes of students of SMP Negeri 13 economic Sijunjung ( 3 ) the influence of the discipline of learning and use of the library together to results SMP students studying economics Sijunjung 13 .The population in this study were students Seventh Grade Students of SMP Negeri 13 Sijunjung . Determination of sample size using the formula Slovin with a total sample of 87 students . While the retrieval technique used is proportional random sampling . Data analysis techniques using multiple regression tests of significance using the t test and F test while using the classical assumption normality test , test Heterokedastitas , Multikoloneritas test and autocorrelation test .These results indicate that ( 1 ) the discipline of learning significantly affect the economics student learning outcomes SMP 13 Sijunjung . It can be seen from the sig value of 0.001 < Î± = 0.05 and regression coefficient b = X1 ( 0.272 ) , ( 2 ) use of the library significantly affect the economics student learning outcomes SMP 13 Sijunjung because it has a sig of 0000 < Î± = 0.05 , and the coefficient of linear regersi b = X2 ( 0.881 ) ( 3 ) discipline of learning and use of the library together significantly influence the results of the economic study of students of SMP Negeri 13 Sijunjung with sig 0 , 000 < Î± = 0.05 .Based on the results of this study concluded that there is a significant relationship between the discipline of learning and use of the library on learning outcomes of students of SMP Negeri 13 economic Sijunjung . For the next researchers who are interested in researching the same topic , it is advisable to pay attention to other variables that allegedly played a role and menpengaruhi student learning outcomes .Â